ANALISIS PERBANDINGAN KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD PADA INDOSAT DAN XL - Ompi, Pingkan; Budiasih, I.G.A.N (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
This study aims to determine how differences in the performance of Indosat and XL with four perspectives of the balanced scorecard (BSC). Data in this study consist of annual report for 2009- 2012, the organizational structure, vision, mission, and general description of Indosat and XL. Data collection methods used is documentation. The variables of this study are four BSC perspectives. The data analysis technique used is descriptive comparative. Elaboration of the four perspectives indicate that the performance of the financial perspective is XL outperform than Indosat, while the customer perspective and the internal business process perspective is Indosat outperform than XL. In the learning and growth perspective, XL outperform than Indosat at indicator of employee productivity while on the ability of employees of both companies are just as good. Overall performance is directly proportional to Indosat and XL .
Keywords: Balanced Scorecard, Performance, Indosat, XL